Teaching Communicative Translation through Skopos Theory - Yanny Indrawati (Magister Scientiae, 2010)
Communication is considered successful when the people involved understand each others. Since there are many languages around their world, languages can also be a barrier in communicating. People with a particular language cannot interact with other who has different language than his to link this shortage, it requires the role of a translator. Nowadays many people are just taking the opportunity to be translators just because they are bilingual without any awareness of what it is called as successful in translation People with a particular language cannot interact with other who has different language than his. In this regard, this paper will discuss what aspect are necessary to be a professional translator. This understanding will lead us to know how to teach translation to students in order to achieve a communicative translation.